Формування ідентичності районів масової житлової забудови 1960–1980-х pp - Мисак, Наталія Романівна (Національний університет "Львівська політехніка", 2018)
У дисертації проаналізовано особливості національних дискурсів модерністських житлових планувальних одиниць серед яких українські мікрорайони, польські blokowiska, німецькі Großsiedlungen, французькі grand ensemble, шведські bostadsområde från rekordåren. Розроблено теоретичну модель ідентичності районів масової житлової забудови, яка поєднує поняття архітектурна своєрідність, первинна та вторинна ідентичності. Відповідно до неї сформовано методичну модель дослідження на основі підходу змішаних методів з наданням переваги якісним методам над кількісними. Досліджено формування та розвиток району Сихів у Львові в контексті масового будівництва житла в Радянському Союзі й містобудівних перетворень Львова; артикульовано архітектурну своєрідність, первинну і вторинну ідентичності району. Аналогічно, досліджено формування і розвиток району Русенґорд у Мальмо (Швеція) в контексті Програми мільйону у Швеції та повоєнних перетворень Мальмо; артикульовано архітектурну своєрідність, первинну і вторинну ідентичності району. Проведено компаративний аналіз та встановлено деякі взаємозалежності поміж архітектурною ідентичністю і структурними елементами простору районів. Проаналізовано результати архітектурного студіо, процесу партисипативного проектування скверу і конкурсний проект площі у Сихові. запропоновано способи використання концептів первинну та вторинну ідентичності в учасницькому проектуванні й модернізації житлових районів. В диссертации проанализированы особенности национальных дискурсов модернистских жилых планировочных единиц, среди которых украинские мікрорайони, польские blokowiska, немецкие Großsiedlungen, французские grand ensemble, шведские bostadsområde från rekordåren. Разработана теоретическая модель идентичности районов массовой жилой застройки, сочетающая понятия архитектурное своеобразие, первичная и вторичная идентичности. Согласно указанной модели сформирована методическая модель исследования на основе подхода смешанных методов с предпочтением качественных методов по сравнению количественными. Исследовано формирование и развитие района Сыхов во Львове в контексте массового строительства жилья в Советском Союзе и градостроительных преобразований Львова; артикулированы архитектурное своеобразие, первичная и вторичная идентичности района. Аналогично исследовано формирование и развитие района Русенґорд в Мальме (Швеция) в контексте Программы миллиона в Швеции и послевоенных преобразований Мальме; артикулированы архитектурное своеобразие, первичная и вторичная идентичности района. Проведен компаративный анализ и установлены некоторые взаимозависимости между архитектурной идентичностью и структурными элементами пространства районов. Проанализированы результаты архитектурного студио, процесса партисипативного проектирования сквера и конкурсный проект площади в Сыхове. Предложены способы использования концептов первичной и вторичной идентичностей в участническом проектировании и модернизации жилых районов. Thesis offers an review of formation of Modernist movement and key architectural and city planning concepts that laid the foundation for the development of Modernist regional planning units in various countries in Europe. considers peculiarities of national discourses of Modernist housing estates in several European countries that had been parts of different political systems on the example of Ukrainian мікрорайони, Polish blokowiska, German Großsiedlungen, French grand ensemble, Swedish bostadsområde från rekordåren. Theoretical model for the identity of large-scale housing estates that combines both conventional approaches to interpreting identity, and alternative positions that take it as a dynamic context-based construct. The alternative model for the notion of architectural identity was developed on the basis of the concepts of architectural originality, and primary and secondary identities. Methodological model of the research is based on the theoretical model for interpreting architectural identity of Modernist estates on several levels, in line with the Lefebvre’s spatial triad. With regard for the theoretical sub-framework, mixed method approach and qualitative research methods are preferred rather than quantitative methods. Comparative research method was chosen for establishing a common research sub-framework and research discourse for different European contexts. Sykhiv case study considers the estate under analysis in the context of mass housing construction in the Soviet Union and the urban planning transformations in Lviv, and also in line with the theoretical model on the following three levels – of architectural originality, of primary and of secondary identities. Rosengård case study explores a housing estate contextualized in architectural and city planning processes in Sweden, in terms of transformations in the city of Malmö. According to the theoretical model, architectural originality, as well as primary and secondary identities of the area were analyzed. Comparison of contextual peculiarities and transformations of the estates under analysis was made; it reintegrates the results of case studies of Sykhiv and Rosengård. It was used the analysis of architectural originality to distinguish several structural elements of space of different scales enabling descriptions of basic morphological characteristics of the housing estates, correlated with their primary and secondary identities, such as: placement within the city’s structure, boundaries of the neighbourhood, morphology of the area, arterial road, central public space, a residential building, an apartment, a residential yard. It is correlated the notions of identity with the Modernist district as a legacy in Ukrainian context. Outcomes of work of the architectural studio, the process of participatory design of a public garden, as well as a competitive design for a square in Sykhiv are analyzed. Lastly, ways of applying the findings on primary and secondary identities in participatory design and modernization of housing estates on the basis of shaping narratives and direct impact on the development of large-scale housing estates were offered.
Формирование идентичности районов массовой жилой застройки 1960–1980-х гг.
Idenity Formation of Large-Scale Housing Estates Built in the 1960–1980s
Keywords: райони масової житлової забудови; пізній модернізм; Європа; 1960-80 рр.; ідентичність у архітектурі; архітектурна своєрідність; первинна ідентичність; вторинна ідентичність; Україна; Сихів; Швеція; Русенґорд; районы массовой жилой застройки; поздний модернизм; Европа; 1960-80 гг.; идентичность в архитектуре; архитектурное своеобразие; первичная идентичность; вторичная идентичность; Украина; Сыхов; Швеция; Русенгорд; large-scale housing estates; late modernism; Europe; 1960-80s; identity in architecture; architectural originality; Ukraine; Sykhiv; Sweden; Rosengård; 72.02 «1960/1980»